2005
DOI: 10.1073/pnas.0409377102
|View full text |Cite
|
Sign up to set email alerts
|

The two-component signal transduction system RR06/HK06 regulates expression of cbpA in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae encounters a number of environmental niches in the body, including the nasopharynx, lungs, blood, middle ear, and brain. Recent studies have identified 13 putative two-component signal-transduction systems in S. pneumoniae, which are likely to be important for gene regulation in response to external stimuli. Here, we present conclusive evidence for the regulation of choline binding protein A (CbpA), a major pneumococcal virulence factor and protective antigen, by one of these two-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 38 publications
(37 reference statements)
4
53
4
Order By: Relevance
“…For instance, CiaR/ CiaH has been demonstrated to contribute to virulence (25,29), probably in part through control of expression of htrA, which encodes a serine protease that is a major virulence factor (11,19). Recently, TCS06 has been found to regulate the expression of cbpA, which codes for a major adhesin that is also a protective antigen (26).…”
mentioning
confidence: 99%
“…For instance, CiaR/ CiaH has been demonstrated to contribute to virulence (25,29), probably in part through control of expression of htrA, which encodes a serine protease that is a major virulence factor (11,19). Recently, TCS06 has been found to regulate the expression of cbpA, which codes for a major adhesin that is also a protective antigen (26).…”
mentioning
confidence: 99%
“…which is induced by the autoinducible peptide BlpC and controls bacteriocin production (6,32); TCS04, which is involved in the regulation of PsaA (23); and TCS06, which regulates expression of cbpA (35). The only essential response regulator, RR02, regulates expression of PspA (25), and the orphan response regulator, RitR, regulates iron transport (41).…”
mentioning
confidence: 99%
“…A previous study reported that the rr06/hk06 locus is involved in regulating the expression of cbpA (53). We determined if this TCS regulated expression of other pneumococcal genes and virulence factors by transcriptional analysis of an rr06 mutant in laboratory strain R6 by microarray analysis.…”
Section: Resultsmentioning
confidence: 99%